American women in World War I : they also served - Gavin, Lettie, 1922- (Niwot, Colorado : University Press of Colorado, 1997)
"American Women in World War I provides the first comprehensive overview of women's role in the World War I war effort. Through personal interview, and excerpts from diaries, letters, and memoirs, the author relates poignant stories of wartime experiences and provides a unique perspective on the progress of women in military service. Devoting one chapter to each of the nine areas of service, the author interweaves richly detailed personal stories with historical photos and background to create a lively account that captures the heart and spirit of the times."--Provided by publisher
First women of the Navy -- Women Marines -- The Army nurse -- The Hello Girls of the Army Signal Corps -- Reconstruction aides -- Women of the YMCA -- The woman physician in the Great War -- Red Cross volunteers -- The Salvation Army -- Appendix A: Chemical warfare and shell shock -- Appendix B: For the record.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: World War, 1914-1918 -- Women -- United States; Women -- United States -- History -- 20th century; War; Women; Women -- United States -- History -- 20th century; Women; Armed Conflicts; Physicians, Women -- history; United States; Guerre mondiale, 1914-1918 -- Femmes -- États-Unis.; Femmes -- États-Unis -- Histoire -- 20e siècle.; Guerre; wars; armed conflicts; women (female humans); HISTORY -- Military -- World War I; HISTORY -- General; Women; United States; World War, 1914-1918 -- Women -- United States; Women -- United States -- History -- 20th century; 1900-1999; History